2022
DOI: 10.1007/s12011-022-03354-9
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Calcium Titanate or Erbium Oxide Nanoparticles Induced Cytotoxicity and Genotoxicity in Normal HSF Cells

Abstract: Extensive uses of calcium titanate nanoparticles (CaTiO3-NPs) and erbium oxide nanoparticles (Er2O3-NPs) increase their release into the environment and human exposure, particularly through skin contact. However, there are almost no studies available on the effect of these nanoparticles on skin integrity. Therefore, this study was undertaken to estimate CaTiO3-NP- or Er2O3-NP-induced cytotoxicity and genotoxicity in normal human skin fibroblast (HSF) cells. Cell viability was measured using sulforhodamine B (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…colleagues26 of the high cytotoxicity and non-genotoxic effects of Er 2 O 3 -NPs towards normal human skin fibroblasts (HSF) cells are attributable to genomic stability and controlled DNA repair mechanisms, thus normal HSF cells maintain their genomic integrity.…”
mentioning
confidence: 99%
“…colleagues26 of the high cytotoxicity and non-genotoxic effects of Er 2 O 3 -NPs towards normal human skin fibroblasts (HSF) cells are attributable to genomic stability and controlled DNA repair mechanisms, thus normal HSF cells maintain their genomic integrity.…”
mentioning
confidence: 99%
“…Although, the size of many nanoparticles measured by DLS is actually found to be larger than the size measured by TEM, there is no fixed rule for nanoparticles because the measured size of nanoparticles depends on the concentration of nanoparticles, ions and other variables. Consequently, the lower measured size of CaTiO 3 -NPs in this study by Dynamic Laser Scattering (DLS) compared to that measured by TEM in our recent published manuscript [ 19 ] may result from using highly diluted samples in DLS and also the low Zeta potential value of − 3.38 mv makes CaTiO 3 -NPs highly aggregated in consistence with recent study [ 20 ] that showed that size of CaTiO 3 -NPs by DLS was ranged from 15–30 nm, while sized measured by TEM was larger and ranged from 10–100 nm.…”
Section: Discussionmentioning
confidence: 78%
“…Similarly, treatment of normal cells with CaTiO 3 -NPs caused the time and concentration-dependent death of normal human skin fibroblast (HSF) cells. However, the genomic integrity of normal HSF cells was still normal and not disrupted after treatment with IC50/72 of CaTiO 3 -NPs for 72 h [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Calcium titanate microspheres, calcium titanate composites, calcium titanate NPs / Electrochemical biosensing, [89] bone tissue engineering, [90] dental implant surface modification, [91] peripheral nerve regeneration. [92] Antibacterial property, bone-bonding capabilities, [91] Cytotoxicity [93] Melanin Eumelanin, polydopamine…”
Section: (Continued)mentioning
confidence: 99%